1976
DOI: 10.1093/infdis/133.3.343
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Production of Respiratory Tract Infection with Mycoplasma pneumoniae in Rhesus Monkeys

Abstract: Knowledge of the pathogenesis of pneumonia due to Mycoplasma pneumoniae has been derived primarily from experimental infection of rodents. As part of an effort to establish a model with a closer resemblance to man, three seronegative, young, adult rhesus monkeys (Macaca mulatta) were inoculated with M. pneumoniae (10(7.4) cfu per animal) by oropharyngeal administration of coarse-particle aerosol. Five to six days after exposure of the animals, cultures obtained from the upper respiratory tract were positive fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1979
1979
2012
2012

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Reports of infection in nonhuman primates have been primarily on experimental infections. Rhesus can be infected, but without clinical signs (Friedlaender et al, 1976). There was no transmission between infected and control animals, although the organism persisted in infected rhesus for up to 50 days.…”
Section: Mycoplasma Pneumoniaementioning
confidence: 94%
“…Reports of infection in nonhuman primates have been primarily on experimental infections. Rhesus can be infected, but without clinical signs (Friedlaender et al, 1976). There was no transmission between infected and control animals, although the organism persisted in infected rhesus for up to 50 days.…”
Section: Mycoplasma Pneumoniaementioning
confidence: 94%
“…pneumoniae. M. pneumoniae PI-1428 was used previously to experimentally infect guinea pigs (11,12), hamsters (2, 3), Cercopithecus (African green) and Macaca (rhesus) monkeys (28), human volunteers (19,48,49), and chimpanzees (4, 5). Strain PI-1428 was also shown to attach avidly to cell cultures (14,17).…”
Section: Methodsmentioning
confidence: 99%
“…Although not determined, the mode of transmission was probably (i) an aerosol from an inoculated, infected chimpanzee to a control; (ii) an aerosol from an inoculated, infected chimpanzee through a caretaker to a control; or (iii) an instrument fomite, such as a contaminated bronchoscope. In the monkey animal model, Friedlaender et al (28) reported that control monkeys housed together with cage mates experimentally infected with M. pneumoniae did not become colonized (28). This suggests that chimpanzees may be more susceptible to infection with M pneumoniae than monkeys are.…”
Section: Methodsmentioning
confidence: 99%
“…Mycoplasma pneumoniae is a common cause of communityacquired pneumonia transmitted by aerosol or close contact (Friedlaender et al, 1976). Major outbreaks occur periodically and the severity of clinical symptoms ranges from asymptomatic to pronounced pneumonia (Clyde, 1993).…”
Section: Introductionmentioning
confidence: 99%